2012
DOI: 10.1017/s1368980012004818
|View full text |Cite
|
Sign up to set email alerts
|

Adopting and implementing nutrition guidelines in recreational facilities: tensions between public health and corporate profitability

Abstract: Objective: Little is known about how public entities can partner with industry to achieve public health goals. We investigated industry's perspective of factors that influenced their adoption and implementation of voluntary, governmentissued nutrition guidelines (Alberta Nutrition Guidelines for Children and Youth, ANGCY) in recreational facilities. Design: In-depth semi-structured interviews were conducted. Data were analysed using directed content analysis. Setting: Food services in recreational facilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 23 publications
3
51
0
Order By: Relevance
“…Indeed, recreation stakeholders in this study and the pilot study emphasized that change takes time. 12 In interviews, intervention communities reported a number of barriers that may have influenced the amount of change that they were able to achieve in their vending 25 and that are similar to those reported in other studies, 11,12,15,31 including: (1) limited availability of healthy vending machine products; (2) being locked into contracts that did not require vendors to offer healthier choices; (3) unwillingness of vendors to make changes; (4) few suppliers of healthy options; (5) low sales of healthy options; (6) concerns about lower profit margins on healthy products (although sales data were not collected in this study to validate this concern); and (7) limited time to ensure machines contained healthy choices.…”
Section: Discussionmentioning
confidence: 54%
“…Indeed, recreation stakeholders in this study and the pilot study emphasized that change takes time. 12 In interviews, intervention communities reported a number of barriers that may have influenced the amount of change that they were able to achieve in their vending 25 and that are similar to those reported in other studies, 11,12,15,31 including: (1) limited availability of healthy vending machine products; (2) being locked into contracts that did not require vendors to offer healthier choices; (3) unwillingness of vendors to make changes; (4) few suppliers of healthy options; (5) low sales of healthy options; (6) concerns about lower profit margins on healthy products (although sales data were not collected in this study to validate this concern); and (7) limited time to ensure machines contained healthy choices.…”
Section: Discussionmentioning
confidence: 54%
“…options in the 'Choose Most Often' category) but continued to allow unhealthy choices to be sold alongside them. According to Olstad et al (59) , this proved to be the most important barrier to the policy's achievement of meaningful change in facility food environments (62) . Observations of children within the facilities examined revealed that they were also still more likely to make unhealthy choices (62) .…”
Section: Recreation and Sport Settingsmentioning
confidence: 99%
“…According to Olstad et al (59) , this proved to be the most important barrier to the policy's achievement of meaningful change in facility food environments (62) . Observations of children within the facilities examined revealed that they were also still more likely to make unhealthy choices (62) . Thus, it is clear that the implementation of nutrition guidelines in these settings is complex, that strong government action is required in order for their effect to be gleaned at the population level, and that monitoring and evaluation are essential to support meaningful change in this area (59,61) .…”
Section: Recreation and Sport Settingsmentioning
confidence: 99%
“…Olstad and colleagues conducted a series of mixed-methods studies evaluating the adoption of healthy food guidelines in public recreation facilities in Canada, finding difficulties in implementation and acceptance. [27][28][29][30] With the frequency and timing of games and practices, ensuring a healthy environment at sporting events will support the well-being of players and families. Engaging families, coaches, and stakeholders will be an important step in establishing policies to improve the food environment of youth sports.…”
Section: Childhood Obesity June 2014mentioning
confidence: 99%